2020
DOI: 10.1113/jp280294
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐stimulated glucose uptake partly relies on p21‐activated kinase (PAK)2, but not PAK1, in mouse skeletal muscle

Abstract: Muscle-specific genetic ablation of p21-activated kinase (PAK)2, but not whole-body PAK1 knockout, impairs glucose tolerance in mice. r Insulin-stimulated glucose uptake partly relies on PAK2 in glycolytic extensor digitorum longus muscle r By contrast to previous reports, PAK1 is dispensable for insulin-stimulated glucose uptake in mouse muscle.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 72 publications
(178 reference statements)
1
22
0
Order By: Relevance
“…PAK1 KO mouse muscles also displayed diminished insulin-stimulated GLUT4 translocation (Wang et al, 2011). On the other hand, another study reported normal insulin-stimulated glucose uptake in vivo and in isolated muscle of PAK1 KO mice, whereas insulin-stimulated glucose uptake was slightly reduced in muscle-specific PAK2 KO mice (Møller et al, 2020).…”
Section: Insulin Signaling To Glut4 In Musclementioning
confidence: 94%
See 1 more Smart Citation
“…PAK1 KO mouse muscles also displayed diminished insulin-stimulated GLUT4 translocation (Wang et al, 2011). On the other hand, another study reported normal insulin-stimulated glucose uptake in vivo and in isolated muscle of PAK1 KO mice, whereas insulin-stimulated glucose uptake was slightly reduced in muscle-specific PAK2 KO mice (Møller et al, 2020).…”
Section: Insulin Signaling To Glut4 In Musclementioning
confidence: 94%
“…Whether PAK1 is required for insulin-stimulated glucose uptake in skeletal muscle is so far controversial. On one hand, pharmacological inhibition of PAK isoforms abolished insulinstimulated GLUT4 translocation and glucose uptake in myoblasts and myotubes (Tunduguru et al, 2014) and partially reduced the glucose response in mouse skeletal muscle (Møller et al, 2020). PAK1 KO mouse muscles also displayed diminished insulin-stimulated GLUT4 translocation (Wang et al, 2011).…”
Section: Insulin Signaling To Glut4 In Musclementioning
confidence: 99%
“…In addition, several studies have linked both PAK1 and PAK2 to the regulation of glucose homeostasis [ 51 , 52 , 53 ]. However, a recent study by the Sylow lab challenges this, suggesting that insulin-stimulated glucose uptake relies partly on PAK2, but not PAK1 [ 54 ]. Glucose tolerance in vivo and the insulin-stimulated uptake of 2-deoxy-D-glucose into extensor digitorum longus muscle ex vivo were mildly impaired in mice lacking PAK2, but not PAK1, using muscle-specific deletion [ 54 ].…”
Section: Rho Family Gtpases and Rho Gefsmentioning
confidence: 99%
“…However, a recent study by the Sylow lab challenges this, suggesting that insulin-stimulated glucose uptake relies partly on PAK2, but not PAK1 [ 54 ]. Glucose tolerance in vivo and the insulin-stimulated uptake of 2-deoxy-D-glucose into extensor digitorum longus muscle ex vivo were mildly impaired in mice lacking PAK2, but not PAK1, using muscle-specific deletion [ 54 ]. In addition to WAVE and PAKs, Rac1 also activates the cofilin phosphatase slingshot1 (Ssh1), leading to cofilin inactivation [ 55 ].…”
Section: Rho Family Gtpases and Rho Gefsmentioning
confidence: 99%
“…There are six members in PAKs family, which are divided into two groups based on the sequence and structure homology: group I PAKs (including PAK1, PAK2, and PAK3) and group II PAKs (including PAK4, PAK5, and PAK6). Among all PAKs, PAK1, and PAK4 have been well studied, and other PAKs are getting researchers’ interest ( Geng et al, 2020 ; Maruta and Kittaka, 2020 ; Møller et al, 2020 ; Ruan et al, 2020 ; Zheng et al, 2020 ). Most of the PAKs have oncogenic effects on cancer development.…”
Section: Introductionmentioning
confidence: 99%